The impact of baseline laboratory tests on the management of new-onset hypertension in primary care: A pilot study - Katia Kteich; Maria R. Karam; Marouan Zoghbi; Mabel Aoun (PLoS ONE, 2025)
Background Hypertension is a key contributor to the global cardiovascular disease burden. In 2021, the World Health Organization (WHO) hypertension management guideline suggested baseline laboratory tests for patients with newly diagnosed hypertension but noted limited evidence in primary care contexts. This study evaluates the impact of baseline laboratory assessments on blood pressure control and comorbidities in newly diagnosed hypertensive patients. Methods This is a multicenter retrospective study that included all patients with new-onset hypertension between January 2015 and January 2020, followed in three primary health care centers until 2022. Data collection included 8 items of paraclinical tests performed at the diagnosis of hypertension: serum sodium, potassium and creatinine, lipid panel, electrocardiogram, glucose, HbA1c and urine dipstick. Complete workup was defined as having the 8 items checked and partial workup included 1–7 items. Blood pressure was assessed at one year and the final visit, which was beyond one year, in the two workup groups. Results Of 621 hypertensive patients, 107 with incident hypertension were analyzed (mean age: 54.8 ± 12.7 years; 58.9% women). A complete workup was done for 48 patients, partial for 52 and none for 7. Abnormalities detected included: 8.4% of patients with fasting blood glucose > 125 mg/dL, 7.5% with HbA1c > 6.5%, 1.9% with serum potassium < 3.5 mmoL/L, 54.2% with LDL Cholesterol > 100 mg/dL, 35.5% with serum creatinine > 0.8 mg/dL, and 7.5% with an estimated GFR < 60 mL/min/1.73 m2. Significant systolic blood pressure improvement was seen at 12 months in the complete workup group (129.9 ± 13.6 mmHg) vs. partial workup group (142.8 ± 18.9 mm Hg) (P = 0.003). Men and smokers were tested more often than women and non-smokers. Conclusion Baseline laboratory tests in patients with newly diagnosed hypertension help unmask comorbidities such as chronic kidney disease, diabetes, and dyslipidemia. Our findings support the use of baseline laboratory testing in order to optimize blood pressure control and individual patient management.